7(0)-7y=49

Simple and best practice solution for 7(0)-7y=49 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(0)-7y=49 equation:


Simplifying
7(0) + -7y = 49

Multiply 7 * 0
0 + -7y = 49

Anything times zero is zero.
0 + -7y = 49
Remove the zero:
-7y = 49

Solving
-7y = 49

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Divide each side by '-7'.
y = -7

Simplifying
y = -7

See similar equations:

| 3x+11=75-5x | | 2d=d+7 | | 3a-5=5-a | | 7x+5(2x-7)=169 | | 55-3x=15x+21 | | 6h+5=5h | | 7-7x=57-42x | | 6(7)+7y=84 | | -5r-9=-9r+7 | | 10x+12x=440 | | -59+10x=9x+17 | | 28r-6(3r-5)=40 | | 2(3x+1)=7x+4 | | 6x+7(0)=84 | | 4x+6=-71-7x | | c-2=-8c+9+7 | | 0.5k+22=38 | | 6(0)+7y=84 | | 6x+35=8x+11 | | x^2+7=0 | | 9g+5=50 | | 15-4(3c+2)=13 | | y=x+6 | | 10-4y=7-6y | | 72-4n=-22n | | 2-6c=9-7c | | 3v^2=9v | | -4k=-3k+8 | | -9a=-12a-45 | | -3z+8+[-2z]=-12 | | w^2=4 | | 5n=8+6n |

Equations solver categories